REFLEXIVE STABILITY OF THE MONETARY SYSTEM AND THE CENTRAL BANK POLICY - O. I. Rumyantseva (Финансы: теория и практика)
Nowadays, the reflexivity of the monetary system is an important factor in shaping the demand for national money, because it is the behavior of economic agents and their confidence in the monetary regulator and the monetary policy that finally determines the reflexive stability of the latter. This is especially true of monetary processes significantly affected by subjective factors, namely views of the participants on current events. The author gives a definition of the reflexive stability of the monetary system, the role of the post-nonclassical management paradigm to achieve it as well as the place of the communication policy of monetary control in the design and implementation of the monetary policy.